Electrochemotherapy in treatment of canine oral malignant melanoma and factors influencing treatment outcome - Tellado, Matías Nicolás (2020)
Oral malignant melanoma is the most common, but aggressive oral cancer in dogs with poor prognosis. Electrochemotherapy (ECT) has therapeutic potential in such tumors as effective local treatment. Therefore, the aim of this prospective clinical study was to evaluate treatment effectiveness of ECT in as first line treatment for canine oral malignant melanoma, and search for factors influencing treatment outcome. Sixty-seven canines with primary oral malignant melanoma, non-candidates for first-line therapy, were enrolled. All dogs received ECT and follow-up exams for the span of two years. Based on RECIST criteria, the objective response rate was 100%, 89.5%, 57.7%, and 36.4%, in stage I, II, III and IV, respectively. Only patients in stage I, II and III with partial or complete response improved their quality of life. The median time to progression was 11, 7, 4 and 4 months, and median survival time after the treatment was 16.5, 9.0, 7.5 and 4.5 months, for patients in stage I, II, III and IV, respectively. Significantly better was local response in stage I and II disease (p = 0.0013), without the bone involvement (p = 0.043) Electrochemotherapy is effective local treatment of oral canine malignant melanoma when no alternative treatment is available. Better response is expected in stage I and II patients with tumors without bone involvement.